PROBLEM SOLVING IN THE CONTEXT OF COMPUTATIONAL THINKING - Swasti Maharani; Muhammad Noor Kholid; Lingga Nico Pradana; Toto Nusantara (IKIP Siliwangi and I-MES, 2019)
Computational thinking is needed in the 21st century, where we live in an era of digitalization. Also, there is a global movement to incorporate computational thinking into the education curriculum, especially Mathematics education. The different of this research with others is this research compares the Polya problem solving and computational thinking. This research was conducted to find out how the relationship/relationship of the Polya problem-solving with the steps of computational thinking. The method used in this research is descriptive qualitative. The subject of this study was mathematics education students. The results showed that the relationship between problem-solving and computational thinking of respondent when solving the problem is when defining the problem in the context of problem-solving, the respondent performs the stage of decomposition and abstraction in the context of computational thinking. During the planning process of the solution process, respondents carried out the generalization stage. When the scene is carrying out the plan and the problem solver to look back to evaluate the solution, the respondent performs the debugging and algorithmic steps.